2012
DOI: 10.1007/s10329-012-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-related behavior of orphan chimpanzees (Pan troglodytes schweinfurthii) at Gombe National Park, Tanzania

Abstract: This study examined the anxiety levels and social interactions of two orphan and four mother-reared adolescent chimpanzees (Pan troglodytes schweinfurthii) in the Kasekela community at Gombe National Park, Tanzania. We used focal sampling in the field at Gombe to observe these adolescent individuals. Their social interactions and anxious behavior, measured as rough scratching, were recorded. The two orphans differed from others of a similar age by exhibiting higher levels of anxiety and lower levels of play. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
1
21
1
1
Order By: Relevance
“…Although there are several neural circuits affected by early-life adversity, the amygdala is a suitable choice for discussion because it develops early in postnatal life (Gilmore, et al, 2012; Humphrey, 1968; Ulfig, Setzer, & Bohl, 2003) mediates many of the emotional difficulties exhibited by those who experienced early-life adversity (e.g., hyper-emotionality), and because it is rich with stress hormone receptors particularly in early postnatal life (Avishai-Eliner, Yi, & Baram, 1996; Baram & Hatalski, 1998; Fenoglio, Brunson, Avishai-Eliner, Chen, & Baram, 2004; Moriceau, et al, 2004; Vazquez, et al, 2006). Youths who have experienced early caregiver deprivation tend to be highly anxious (Casey, et al, 2009; Goff, et al, 2012; Tottenham, et al, 2010; Zeanah, et al, 2009), as has been found in other species that have experienced maternal deprivation (Berman, Rasmussen, & Suomi, 1994; Botero, Macdonald, & Miller, 2013; Caldji, et al, 1998; Callaghan & Richardson, 2013; Macri, Laviola et al, 2010; Sabatini, et al, 2007). Youths with a history of early neglect have exhibited enlarged amygdala volumes in samples that have included PI youths (Mehta, et al, 2009; Tottenham, et al, 2010; but see Sheridan, Fox, Zeanah, McLaughlin, & Nelson, 2012) and youths whose mothers with post-partum depression (and presumably would have provided little direct caregiving)(Lupien, et al, 2011).…”
Section: The Development Of Affective Behaviors (Humans)mentioning
confidence: 63%
“…Although there are several neural circuits affected by early-life adversity, the amygdala is a suitable choice for discussion because it develops early in postnatal life (Gilmore, et al, 2012; Humphrey, 1968; Ulfig, Setzer, & Bohl, 2003) mediates many of the emotional difficulties exhibited by those who experienced early-life adversity (e.g., hyper-emotionality), and because it is rich with stress hormone receptors particularly in early postnatal life (Avishai-Eliner, Yi, & Baram, 1996; Baram & Hatalski, 1998; Fenoglio, Brunson, Avishai-Eliner, Chen, & Baram, 2004; Moriceau, et al, 2004; Vazquez, et al, 2006). Youths who have experienced early caregiver deprivation tend to be highly anxious (Casey, et al, 2009; Goff, et al, 2012; Tottenham, et al, 2010; Zeanah, et al, 2009), as has been found in other species that have experienced maternal deprivation (Berman, Rasmussen, & Suomi, 1994; Botero, Macdonald, & Miller, 2013; Caldji, et al, 1998; Callaghan & Richardson, 2013; Macri, Laviola et al, 2010; Sabatini, et al, 2007). Youths with a history of early neglect have exhibited enlarged amygdala volumes in samples that have included PI youths (Mehta, et al, 2009; Tottenham, et al, 2010; but see Sheridan, Fox, Zeanah, McLaughlin, & Nelson, 2012) and youths whose mothers with post-partum depression (and presumably would have provided little direct caregiving)(Lupien, et al, 2011).…”
Section: The Development Of Affective Behaviors (Humans)mentioning
confidence: 63%
“…Note, however, that female primates are much more likely to suffer from a lack of maternal support than to benefit from it, not only in terms of rank outcomes (Fig. 2), but also in terms of behavioural and social development (Botero et al, 2013; Clay & de Waal, 2013; Missakian et al, 1972), as well as mortality risk (Hasegawa & Hiraiwa, 1980). …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that early deprivation and social isolation in orphan wild-born chimpanzees influence their future development and rehabilitation (Botero et al 2013;Ongman et al 2013). Orphan wild chimpanzees are more susceptible to stress than mother-reared or late-deprived chimpanzees (Reimers et al 2007).…”
Section: Influences On Recoverymentioning
confidence: 96%